Improved Language Reading Ability Using Word Card Media in Low Class MI As Syauqi, Kalimantan Timur - Juhairiah (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2020)
There are 4 language skills in Bahasa. These skills are listening skills, speaking skills, reading skills, and writing skills. Reading skills is very difficult than other language skills. It is difficult because reading skills involve many things, such as: Visual, Think, Psycholinguistic and metacognitive. In Elementary School or Madrasah Ibtidaiyah especially in the first grade, reading is more often acquired because it is how to get to know a letters and letter sound to the children. In this case, student should be try to speak the letter, syllable, word, and it will be expose into writing and oral (how to produce sound letter). Reading, in the lower class’s student is different with the upper class’s student. Lower class student usually has a short concentrate they need an equip and media, it can make the student in the lower class so they can interest in Bahasa Indonesia. Word card is an interesting learning media for student in the lower class especially for reading. By media, reading class is more attractive for the lower class’s student attention. It has the variation method learning process. Dalam bahasa yang kita tahu, ada 4 keterampilan bahasa. Keterampilan ini adalah keterampilan mendengarkan, keterampilan berbicara, keterampilan membaca, dan keterampilan menulis. Keterampilan membaca sangat sulit daripada keterampilan bahasa lainnya. Ini sulit karena keterampilan membaca melibatkan banyak hal, seperti: Visual, Think, Psycholinguistic dan Metacognitive. Di Sekolah Dasar atau Madrasah Ibtidaiyah terutama di kelas satu, bacaan lebih sering didapat karena cara mengenal huruf dan huruf terdengar kepada anak-anak. Dalam hal ini, siswa harus mencoba untuk berbicara huruf, suku kata, kata, dan itu akan mengekspos ke dalam tulisan dan lisan (cara menghasilkan surat suara). Membaca, pada siswa kelas bawah berbeda dengan siswa kelas atas. Siswa kelas bawah biasanya memiliki konsentrasi pendek yang mereka butuhkan peralatan dan media, itu dapat membuat siswa di kelas bawah sehingga mereka dapat tertarik pada bahasa Indonesia. Word card adalah media pembelajaran yang menarik bagi siswa di kelas bawah terutama untuk membaca. Oleh media, kelas membaca lebih menarik untuk perhatian siswa kelas bawah. Ini memiliki metode variasi proses pembelajaran. Keywords: language, reading, word card